7s-10=-3

Simple and best practice solution for 7s-10=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7s-10=-3 equation:


Simplifying
7s + -10 = -3

Reorder the terms:
-10 + 7s = -3

Solving
-10 + 7s = -3

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 7s = -3 + 10

Combine like terms: -10 + 10 = 0
0 + 7s = -3 + 10
7s = -3 + 10

Combine like terms: -3 + 10 = 7
7s = 7

Divide each side by '7'.
s = 1

Simplifying
s = 1

See similar equations:

| 3-4r+2=2r-6(r-3) | | 80=-5(2x-4)-5x | | 2-7r+7=2r-9(r-1) | | -5x-2y=-14 | | 10t-3-t=3+9t | | -2+3x=-y | | -2(x+2)-5=-2x+1 | | -4+x=5 | | 6v=5.4 | | 6.5k+5-5.5k=14 | | x+4y=-26 | | x+1.25=-2.50 | | 5*(2x-3)=x(8-x) | | 12x+11=-13 | | 9.5=x+4.2 | | x(x+6)=24 | | 8x-3(x-5)=30 | | 12x+19=-17 | | -2d-7=11 | | 2x-10+4x+10=50 | | 10x+32=-18 | | X^2-21X+1=0 | | 8y-3=5(2y+2) | | 12x+13=-11 | | 3t^2-12t+4=0 | | 2+9x+8=46 | | 5x+3=4x-12 | | t^3-5t^2-36t=0 | | 56=16+2w | | x+1.66666667=.8333333333x | | 18-a=a | | 8y+5=3y+25 |

Equations solver categories